ربا القرض في المعاملات المعاصرة في ميزان الإقتصاد الإسلامي - Daud Rasyid; Aisyah Daud Rasyid (Universitas Islam Negeri Jakarta, 2017)
Borrowing is a transaction that has been taking place from the earliest human civilisation. Islam encourages its followers to lend others who need it and promises big reward. Islam prohibits any exploitation of people in difficulty by asking for more than what has been borrowed, in any form, either in the form of additional money or in services. In current modern era, someone cannot escape from Bank as an institution that provides a product of lending money to their customers. However, the compensation of the loan is the Bank requires additional payment in some percentage on top of the capital that being borrowed as per defined in the loan agreement when customer pay off the loan, either paying with cash or instalment. The Bank will apply a charge to the borrower when the repayment of the instalments or the pay off is overdue. There are also additional charges such as administration fee that is charged to the customers. DOI: 10.15408/ajis.v17i2.6235